Overview of character education design in senior high schools with boarding school in Indonesia - Fitri, Wanda; Nasril , Nasril; Elvina, Siska Novra; Basra, Sri Meiweni; Syifa, Rizqa Asrarus (COUNS-EDU: The International Journal of Counseling and Education, 2024)
The deployment of character education within Islamic-oriented public boarding schools throughout Indonesia has experienced significant expansion, encompassing both primary and secondary educational tiers. Originally initiated by private entities, this boarding school paradigm has now been embraced by public educational institutions, many of which have emerged as prominent leaders in the field. This educational framework draws inspiration from traditional Islamic boarding schools (pesantren) and prioritizes character development through the integration of religious-humanist principles that are ingrained in everyday practice. The objective of this study is to investigate the framework of character education in state senior high schools that implement the boarding school model. Employing a qualitative research methodology, data were gathered via observational techniques and structured interviews. The results indicate that character education is cultivated through a cohesive and continuous curriculum that interlinks academic instruction with dormitory living experiences. Values are enhanced through systematically organized school programs and are further reinforced by routine dormitory engagements. The institutions also advocate for moral advancement through the cultivation of spiritual consciousness and foster a cohesive culture that bridges academic pursuits with residential life. Furthermore, extracurricular initiatives are utilized to develop not only ethical comprehension but also the social competencies and soft skills of students. These findings underscore the potential efficacy of the boarding school model in promoting comprehensive character development within public educational frameworks.